2014
DOI: 10.1016/j.bpj.2014.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent Cationic Channel Activity in the Inner Membrane of Nuclei from Skeletal Muscle Fibers

Abstract: Nuclear ion channels remain among the least studied and biophysically characterized channels. Although considerable progress has been made in characterizing calcium release channels in the nuclear membrane, very little is known regarding the properties of nuclear monovalent cationic channels. Here, we describe a method to isolate nuclei from adult skeletal muscle fibers that are suitable for electrophysiological experiments. Using this approach, we show for the first time, to our knowledge, that a nuclear mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that myonucleus comprises 50–60% of total nuclei in rat SOL muscle, while myosatellite, vascular endothelial, smooth muscle and nerve cell nuclei account for approximately 2–5%, 10–20% and 20%, respectively [ 23 ]. Morphologically, myonuclei are described as ellipsoidal in shape with a length-to-width ratio of 2.4–4.2 [ 24 ]. In our study, we isolated nuclei from SOL muscle and observed them under a microscope, as shown in Figure 2 A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that myonucleus comprises 50–60% of total nuclei in rat SOL muscle, while myosatellite, vascular endothelial, smooth muscle and nerve cell nuclei account for approximately 2–5%, 10–20% and 20%, respectively [ 23 ]. Morphologically, myonuclei are described as ellipsoidal in shape with a length-to-width ratio of 2.4–4.2 [ 24 ]. In our study, we isolated nuclei from SOL muscle and observed them under a microscope, as shown in Figure 2 A.…”
Section: Resultsmentioning
confidence: 99%
“…It implies that the Ca 2+ release from nuclear envelope into nucleocytoplasm is enhanced in skeletal muscle cell after hindlimb unloading. IP 3 R channel (subtype 1, IP 3 R1) is also located on the INM and release Ca 2+ from nuclear envelope after binding with IP 3 [ 24 , 39 ]. IP 3 R plays an important role in controlling nuclear Ca 2+ level.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that the IP 3 R1 (inositol 1,4,5-triphosphate receptor type 1) is required for the induction of LCSs in skeletal muscle fibers of mice after a hypotonic treatment (Tjondrokoesoemo et al, 2013 ). Single channel recordings of the IP 3 R in isolated nuclei of muscle cells have been described (Kusnier et al, 2006 ) and a large conductance, IP 3 sensitive channel in the inner membrane of nuclei has recently been reported in adult skeletal muscle (Yarotskyy and Dirksen, 2014 ).…”
Section: Introductionmentioning
confidence: 99%